1997
DOI: 10.1111/j.1525-1314.1997.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermobarometry of phengite‐bearing eclogites in the Dabie Mountains of central China

Abstract: A B S TR A CT Pressure-temperature conditions for formation of the peak metamorphic mineral assemblages in phengite-bearing eclogites from Dabieshan have been assessed through a consideration of Fe2+-Mg2+ partitioning between garnet-omphacite and garnet-phengite pairs and of the reaction equilibrium celadonite+pyrope+grossular=muscovite+diopside, which incorporates an evaluation of the extent of the strongly pressure-dependent inverse Tschermak's molecule substitution in the phengites. For the latter equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
197
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(205 citation statements)
references
References 39 publications
(14 reference statements)
6
197
1
1
Order By: Relevance
“…The temperature obtained using Powell (1985) geothermometer, however, is systematically 20 40 C higher than that obtained using Krogh (1988) geothermometer for less calcic garnet (Xgrs < 0.35), but it gives a significantly higher temperature for calcic garnet (Xgrs > 0.35). As Carswell et al (1997) pointed out that temperature estimation is better using Powell (1985) geothermometer for less calcic garnet (Xgrs < 0.35), and Krogh (1988) geothermometer for calcic garnet (Xgrs > 0.35), and we concur with their suggestion. The KD Xgrs relationships used to the temperature estimation of the Sesia samples in the literature is also plotted in Figure 9 (Ungaretti et al, 1983;Oberha nsli et al, 1985;Pognante et al, 1987;Castelli, 1991).…”
Section: Clinopyroxene Data Equilibrated At T 500 C and P = 15 Kbarsupporting
confidence: 80%
“…The temperature obtained using Powell (1985) geothermometer, however, is systematically 20 40 C higher than that obtained using Krogh (1988) geothermometer for less calcic garnet (Xgrs < 0.35), but it gives a significantly higher temperature for calcic garnet (Xgrs > 0.35). As Carswell et al (1997) pointed out that temperature estimation is better using Powell (1985) geothermometer for less calcic garnet (Xgrs < 0.35), and Krogh (1988) geothermometer for calcic garnet (Xgrs > 0.35), and we concur with their suggestion. The KD Xgrs relationships used to the temperature estimation of the Sesia samples in the literature is also plotted in Figure 9 (Ungaretti et al, 1983;Oberha nsli et al, 1985;Pognante et al, 1987;Castelli, 1991).…”
Section: Clinopyroxene Data Equilibrated At T 500 C and P = 15 Kbarsupporting
confidence: 80%
“…This P T estimations are consistent with the occurrence of paragonite inclusion in garnet and omphacite. The combination of the reaction (1) and Grt Cpx geothermometer (GCPQ), that has been extensively employed for the P T estimation of HP rocks (e.g., Carswell et al, 1997;Cuthbert et al, 2000;Nowlan et al, 2000), gives slightly more scattered P T conditions of 2.2 2.5 GPa/665 830 °C than the GCKPQ geothermobarometer. Enami (1996) and Ota et al (2004) reported P T conditions of 1.9 2.6 GPa/700 760 °C for the kyanite quartz eclogite and 1.4 2.5 GPa/550 790 °C for eclogite assemblages from the Western and Eastern Iratsu bodies, respectively.…”
Section: Geothermobarometrymentioning
confidence: 99%
“…White-filled symbols refer to estimates for the barroisite-bearing eclogite, whereas small gray-filled symbols are estimates for the barroisite-free eclogite. Garnet-clinopyroxene-phengite geobarometry symbols: diamond and plus from Carswell et al (1997) and Ravna and Terry (2004), respectively. White black-filled symbols refer to minimum and maximum values of Si contents in phengite, respectively, from the barroisite-bearing eclogite.…”
Section: Prograde Stage (M1 and M2)mentioning
confidence: 99%
“…The barometries proposed by Carswell et al (1997) and Ravna and Terry (2004) were used to calculate the P condition. The peak pressure and temperature were determined using the pyrope + 2 grossular + 3 celadonite = 6 diopside + 3 muscovite equilibrium in the coexisting garnet, omphacite, and phengite assemblages.…”
Section: Peak Stage (M3)mentioning
confidence: 99%